FILSAFAT TAFSIR AL-QURAN DAN BIBEL - Zaimul Am; Sihabudin Noor (Tadarus Tarbawy Jurnal Kajian Islam dan Pendidikan, 2019)
Hermeneutic methods are a way to understand and interpret sentences or the contents of a sentence. Hermeneutics examines problems, methods and objectives of interpretation or interpretation. This science helps to determine the true meaning of the text accurately and includes factors such as history, culture, cultural diversity, language, and the distance between the formulation of the contents of the text, the interpreter, the context, and others. Hermeneutics is also seen as a science of aids in formulating rules, principles, and methodologies for interpreting religion, scripture and its relationship with society. The interpretation of the Qur‘an has been going on since the early era of Islam, that is, from the time of the Messenger of Allah, the Companions, tabi'in (followers), tabi 'al-tabi'in (followers of followers), and the ulama to the present. Qur‘anic science and the Qur'anic exegesis began to develop since the 2nd century oh hijri and so did the interpretation method of the Qur‘an. This study attempts to explain the use of hermeneutic methods as a form of philosophical interpretation in understanding the Qur‘an. This study also examines the use of hermeneutics in the West, for example in interpreting the Bible as a comparative analysis